Islamic Education Based On Local Wisdom For Strengthening Environmental Awareness: A Study Of The Tbilisi Declaration And The Teachings Of Sunan Muria - Mohammad Dzofir; Wir Durridlo (Pascasarjana UIN Siber Syekh Nurjati Cirebon, 2025)
This study aims to analyze: 1) local wisdom of the Muria region as teaching materials for environmental-based Islamic education; 2) implementation of environmental-based Islamic education in MA NU Raden Umar Said (Manurus) and the Muria Forest Care Community Association (PMPH); and 3) the relevance of environmental-based Islamic education to the objectives of the Tbilisi Declaration and the teachings of Sunan Muria. This study uses a qualitative method with a case study approach. Data collection techniques used are observation, in-depth and unstructured interviews, and documentation. The data analysis technique used is qualitative analysis. The results of the study indicate that: 1) Several aspects of local wisdom in Muria that can be used as teaching materials in the context of environmental-based Islamic education include culture, flora, and fauna contained in the teachings and local traditions of the Muria community; 2) Local wisdom-based Islamic education to strengthen environmental awareness carried out by Manurus is carried out through various activities, both in formal subjects and extracurricular activities such as OSIS, Culinary Arts, Batik Sekar, and Scouts. Meanwhile, PMPH Muria implements environmental education through forest conservation efforts, preserving flora and fauna, and increasing public awareness of the importance of nature conservation; and 3) Islamic education based on local wisdom to strengthen environmental awareness implemented by Manurus and PMPH Muria in accordance with the intent and purpose of the Tbilisi Declaration, and in line with the teachings of Sunan Muria which emphasize the values of simplicity, respect for nature, and environmental preservation as part of the teachings of Islam which is rahmatan lil-alamin.